2007
DOI: 10.1086/518862
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrogen Formation on Amorphous Silicates under Interstellar Conditions

Abstract: Experimental results on the formation of molecular hydrogen on amorphous silicate surfaces are presented for the first time and analyzed using a rate equation model. The energy barriers for the relevant diffusion and desorption processes are obtained. They turn out to be significantly higher than those obtained earlier for polycrystalline silicates, demonstrating the importance of grain morphology. Using these barriers, we evaluate the efficiency of molecular hydrogen formation on amorphous silicate grains und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
94
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 25 publications
14
94
0
Order By: Relevance
“…Several laboratories have worked on H atom irradiation and adsorption on diverse surfaces such as graphite and other carbonaceous material, silicates, and ice mantles (mainly water ice), followed by chemistry leading to H 2 production (e.g. Gavilan et al 2012;Vidali et al 2009;Mennella 2008;Amiaud et al 2007;Perets 2007;Creighan et al 2006, and references therein). Many of these studies focused principally on physisorbed atoms and are in general poorly efficient in producing large H 2 abundances at temperatures above about 30 K. The observation of H 2 formation in astronomical environments with gas at high kinetic temperatures has led to the proposition of a mechanism that necessarily involves chemisorbed H atoms (Habart et al 2005;Cazaux et al 2011;Le Bourlot et al 2012) to overcome the barrier of higher temperature formation, in particular in PDR environments.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…Several laboratories have worked on H atom irradiation and adsorption on diverse surfaces such as graphite and other carbonaceous material, silicates, and ice mantles (mainly water ice), followed by chemistry leading to H 2 production (e.g. Gavilan et al 2012;Vidali et al 2009;Mennella 2008;Amiaud et al 2007;Perets 2007;Creighan et al 2006, and references therein). Many of these studies focused principally on physisorbed atoms and are in general poorly efficient in producing large H 2 abundances at temperatures above about 30 K. The observation of H 2 formation in astronomical environments with gas at high kinetic temperatures has led to the proposition of a mechanism that necessarily involves chemisorbed H atoms (Habart et al 2005;Cazaux et al 2011;Le Bourlot et al 2012) to overcome the barrier of higher temperature formation, in particular in PDR environments.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…Experimental studies for the interaction between H or D with silicate surfaces exist in the literature (Pirronello et al 1997;Perets et al 2007;Vidali et al 2007Vidali et al , 2009), but no experimental estimates for the sticking are indicated. In addition, the assumption of no isotopic effects is usually made.…”
Section: The Experimental Situationmentioning
confidence: 99%
“…These parameters are based on a series of experiments and subsequent analysis, reported in Katz et al (1999), Perets et al (2005) and Perets et al (2007). The attempt rate ν I is often assumed to be equal to 10 12 s −1 .…”
Section: The Interaction Between Hydrogen/deuterium Atoms and Dust Grmentioning
confidence: 99%